MAGNETO cardiography parameters to predict future Sudden Cardiac Death (MAGNETO-SCD) or ventricular events from implantable cardioverter defibrillators: study protocol, design and rationale. Issue 10 (10th October 2020) - Lachlan, Thomas; He, Hejie; Sharma, Kavi; Khan, Jamal; Rajappan, Kim; Morley-Davies, Adrian; Patwala, Ashish; Randeva, Harpal; Osman, Faizel
Abstract : Introduction: Predicting sudden cardiac death (SCD) is challenging as current risk predictors have significant limitations. Evaluating magnetocardiogram (MCG) parameters could be of great value and we plan to assess the capability of a new mobile unshielded MCG device in predicting SCD and ventricular arrhythmias (VA) in patients undergoing implantable cardioverter defibrillator (ICD) implantation. Methods and analysis: A prospective multicentre (University Hospitals Coventry and Warwickshire (UHCW) National Health Service (NHS) Trust/University Hospital North Midlands NHS Trust, UK) observational study evaluating the VitalScan MCG (Creavo Medical Technologies, UK) to predict future VA risk; 270 patients meeting criteria for primary or secondary prevention ICDs (ischaemic or non-ischaemic aetiology) are being recruited. The first patient was recruited September 2019 and the study will be completed at final participant follow-up. The primary endpoint is appropriate ICD therapy for VA, secondary endpoint is SCD. Previous trials using MCG identified late QRS signals/QRS fragmentation as potential indicators of SCD in small samples using large shielded expensive MCG devices that were difficult to use clinically. It is hoped the MAGNETO-SCD trial will show this new MCG device can provide real world risk stratification for SCD/VA risk. The trial has recruited 25 patients (13 with secondary prevention indication) from a single site (UHCW) with recruitment starting at the second site in March 2020. Ethics and dissemination: Research Ethics Committee, Yorkshire and Humber Sheffield Research Ethics Committee UK (Ref: 19/YH/0143) and Health Research Authority (IRAS reference 254466, EDGE ID: 123146) approval received on 17/07/2019. The Medicines and Healthcare products Regulatory Agency approval received 11/07/2019. Results will be disseminated via a peer-reviewed publication and presentation at international conferences. Trial registration numbers: ClinicalTrials.gov Registry (NCT04352816 ) and EU Clinical Trials Registry (EudraCT2019-002994-78).